Pengembangan Manajemen Berbasis Sekolah - Saefrudin, Saefrudin (J-MPI (Jurnal Manajemen Pendidikan Islam), 2017)
Education is an important part of the national development process that helps determine the economic growth of a country. Education is also an investment in human resourcedevelopment, where the improvement of skills and abilities is believed to be a factor supporting human efforts in navigating a life full of uncertainty. The variety of school environment conditions and the varied needs of students in the learning process coupled with Indonesia's highly complex geography, often can not be fully appreciated by the central bureaucracy. Therefore, in the process of improving the quality of education needs to find an alternative model of school management. This led to the birth of the concept of school-based quality improvement management. The purpose of this discussion is to describe the concept of management in accordance withthe needs of schools.Key Word: Development, School Based Management